The Reinforcement of Islam Philanthropy by Means of Waqf Optimizing based on Sukuk - Maspupah, Ima; Hasanah, Shofia Mauizotun (Universitas Islam Indonesia, 2016)
Sukuk has been developed rapidly both in quality and quantity, this can be proved by the rapid development in the international financial landscape and is also regarded as the most successful financial products among Islamic financial institutions in the realm of the world. As one of the long-term financing instruments, sukuk has become an alternative funding to be obtained for the investment and projects for governments and companies. In Indonesia, the SBSN development has an outstanding value of Rp 298 trillion, or equal with 13% from the total debt securities issued by the government in September 2015 which showed the value of Rp 2.306 trillion. Sukuk is essentially certificate of ownership of an asset (real project) that can be used on a large scale to defray the construction of sukuk which are not included into buying and selling securities in secondary market, but a financing. Sukuk has assurance in the form of main asset (collateral assets) and serves as the basis for the issuance of sukuk to avoid riba by the prerequis its elements that be traded. The purpose of this article is to present a solution in optimizing the asset-based sukuk that are asset of utilization waqf endowments given in Indonesia which is not yet optimal. The method used is the study of literature. The conceptis generated in the form of waqf asset utilization as underlying assets for sukuk. Where the sukuk was issued through a Special Purpose Vehicle (SPV) as the representative body nadzirin this Indonesian Waqf Board (IWB) to be leased to investors. Sukuk is expected to support the optimization of endowment assets to be more productive as well as a challenge to change consumption patterns and preferences with their moral filter in the form of awareness of social solidarity. As a result, the concept of Pareto optimum which does not recognize the existence of a solution that does not require the sacrifice of the minority (wealthy) in order to improve the welfare of the majority (poor) do not apply anymore.